Analysis of Income Levels in Paulus Sapiya Negeri Kamarian Primary Timber Forest Product Industry (IPHHK), Kairatu District, West Seram Regency - Nabila Mokhtar; Troice E Siahaya; Mersiana Sahureka (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to determine the level of income at Paulus Sapiya's IPHHK before and during the Covid-19 pandemic. By using the formula of income analysis which is described descriptively. The results showed that before the Covid-19 pandemic, the revenue from the IPHHK Paulus Sapiya sawmill business, namely in 2018-2019, was Rp. 24,525,000 and Rp. 760,125,000. During the Covid-19 pandemic in 2020 and 2021, Paulus Sapiya's IPHHK industrial income was Rp. 36,465,000 and Rp. 27,945,000. Paulus Sapiya's IPHHK income has fluctuated in the last four years. Where the occurrence of fluctuations is influenced by the number of sales and requests received by the industry. Paulus Sapiya's IPHHK, which has been running for a period of four years, is profitable because the ratio of the total costs incurred is less than the income received by the industry.